(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This project is based on solar powered electric wheelchair for physically handicapped people. A user friendly interfacing voice recognition system and obstacle detector sensor and Keypad system has been integrated in this solar powered wheelchair. In this way we have implemented a solar powered wheelchair which can be controlled using voice commands and Keypad with the possibility of detecting obstacles by using obstacle detector sensors. In this wheelchair Keypad is provided for handicapped person for moving easily his her hand. This project indicates great success not only in business sector but also it helps disabled people for better life. This project contains electronic system configuration, a sensor system, a mechanical model, voice recognition control and Keypad control are considered.